Black Chicago's first century - Reed, Christopher Robert (University of Missouri Press, 2005)
"Examines the first one hundred years of African American settlement and achievements in Chicago. It spans the antebellum, Civil War, Reconstruction, and post-Reconstruction periods"--Provided by publisher.